2020
DOI: 10.20546/ijcmas.2020.904.083
|View full text |Cite
|
Sign up to set email alerts
|

Immunological and Cytopathological Assessment of Trichomonas vaginalis Infection in Asymptomatic and Symptomatic Females at Menoufia Governorate, Egypt

Abstract: Trichomonas vaginalis (T. vaginalis) is a common health problem all over the world. The present study aimed to determine the prevalence rate and risk factors of T. vaginalis in females in Menoufia Governorate, Egypt and assess some immunological parameters includingIL-2, IL-17, IL22 and INFᵧ and their relation to cytopathological changes in asymptomatic and symptomatic T. vaginalis infected females. Two hundred females aging between 18 and 50 years' old were classified into two groups: Group I: Asymptomatic fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Hamdy and Hamdy [2] declared that the wet mount and Giemsa stained smear had sensitivities of 16.7% and 50%, respectively, and specificities of 100% and 100%. When compared to the Diamond reference index, Hegazy et al [37] showed that Giemsa stained smear and wet mount detected 30/200 (15%) and 26/200 (13%) positive cases, respectively, with sensitivities of 67%, 58%, and specificities of 100%, and 93.5% respectively. Ibrahim et al [35] also reported that direct wet mount smear and Giemsa stained smear detected six cases, compared to nine by MDM with sensitivity and specificity for both of 66.67% and 100% respectively as compared to the Diamond culture.…”
Section: Discussionmentioning
confidence: 99%
“…Hamdy and Hamdy [2] declared that the wet mount and Giemsa stained smear had sensitivities of 16.7% and 50%, respectively, and specificities of 100% and 100%. When compared to the Diamond reference index, Hegazy et al [37] showed that Giemsa stained smear and wet mount detected 30/200 (15%) and 26/200 (13%) positive cases, respectively, with sensitivities of 67%, 58%, and specificities of 100%, and 93.5% respectively. Ibrahim et al [35] also reported that direct wet mount smear and Giemsa stained smear detected six cases, compared to nine by MDM with sensitivity and specificity for both of 66.67% and 100% respectively as compared to the Diamond culture.…”
Section: Discussionmentioning
confidence: 99%